Laparoscopic management of incisional hernia with special emphasis on intraperitoneal mesh-related complication and advantages over open method - Pankaj Saunakiya; Saurabh Purohit; Jitendra Kumar; Jatin Chauhan (Asian Journal of Medical Sciences, 2024)
Background: Ventral hernias (VHs) occur as a result of weakness in the musculofascial layer of the anterior abdominal wall. The most popular classification is congenital, acquired, incisional, and traumatic. Aims and Objectives: The aim of this study is to compare the effectiveness and safety of open versus laparoscopic repair of incisional hernia and to discuss important controversial issues for both procedures, including patient selection, technique, and operative care for laparoscopic repair of VH, operative time of laparoscopic repair of VH, intraoperative and post-operative complications, post-operative pain, post-operative morbidity, and length of hospital stay. Materials and Methods: This prospective study was done in Maharani Laxmi Bai Medical College; Jhansi between January 2021 and June 2022 including 70 patients of incisional hernia were selected for treatment of hernia repair. Thirty-five patients were subjected to laparoscopic incisional hernia repair and 35 patients were subjected to open incisional hernia repair. Results: The findings of the present study demonstrate that laparoscopic incisional hernia repair was safe and in comparison with open incisional repair comparatively less intraoperative blood loss, less post-operative pain, less post-operative complication, less hospital stay, early return to normal activity, and less recurrence. The incidence of enterotomy was slightly more in an open method which was found non-significant difference (P≥0.05). Hence, it is concluded that laparoscopic incisional hernia repair should be the procedure of choice. Conclusions: Laparoscopic incisional hernia repair was safe and better when compared with open incisional hernia repair.